NEW HISTORICIMS ANALYSIS IN SENSE AND SENSIBILITY NOVEL BY JANE AUSTEN - Fitrianita Febrina Ali; Moon Hidayati Otoluwa (Universitas Muhammadiyah Gorontalo, 2021)
This study focused on the use of Stephen Greenblatt's theory to analyze the novel “Sense and Sensibility” by Jane Austen. This study aims to determine the aspects of the novel by using the New Historicism approach. The method used in this research is descriptive qualitative. The data used is written data and the technique used is reading notes. Based on the results of the data analysis, the researcher found several contexts of New Historicism in the “Sense and Sensibility”, namely historical context, social context, cultural context, and biographical context. Historical context to find out how historical factors contained in the novel are then compared to non-literary texts in that era. Social context to find out how the social situation at that time. Cultural context to find out how the culture of society at that time, and biographical context to compare whether the novel describes the life of Jane Austen in the real life.